MATHEMATICAL MODELING OF THIN FILM GROWTH ON SUBSTRATES, ALLOWING THE CONSTRUCTION OF SOLUTIONS TO INVERSE PROBLEMS ARISING IN THE FRAMEWORK OF THE MODEL, BY COORDINATE TRANSFORMATION METHOD - E. O. Tarasenko; A. V. Gladkov; V. S. Tarasenko; A. V. Shaposhnikov (Современная наука и инновации, 2022)
The development of microelectronics, optoelectronics and other branches of science and technology contributes to progress in the field of film modeling